Mechanism of Ir(III) Catalysed Oxidation of Proline by N-Bromosuccinimide - Prakash Sahay, Ved; Prasad, Janak (Asian Journal of Chemistry, 2012)
Kinetics of oxidation of proline by acidic solution of N-bromosuccinimide in the presence of iridium(III) chloride as catalyst have been studied in the presence of mercuric acetate as Br scavenger. The reaction shows fractional order in both proline and Ir(III) and first order at low [NBS] tends to zero-order at high [NBS]. An inverse first-order in H+ is observed. Addition of mercuric acetate, sodium perchlorate and potassium chloride does not bring about any significant change in the reaction velocity while oxidation rate is decreased with successive addition of succinimide. A suitable mechanism in agreement with observed kinetics is proposed.